Beyond the gradebook: embracing the potentials of teacher assessment identity (TAI) in (re)shaping English language professors’ professional development and success in higher education - Masoomeh Estaji; Farhad Ghiasvand (Language Testing in Asia)
Abstract Teacher assessment identity (TAI) has recently positioned itself in the body of literature on second/foreign language (L2) teacher education research. However, the way it contributes to teachers’ professional performance and professionalism has remained blurry to date. To fill this lacuna, this qualitative study was grounded in a poststructuralist perspective on identity to explore the contributions of TAI to English as a foreign language (EFL) teachers’ professional development and success. To this end, a sample of 21 Iranian university instructors was non-randomly selected to attend an interview and compose a narrative frame. The results of thematic analysis, obtained by MAXQDA software, evinced that TAI had facilitated the participants’ professional development by “promoting assessment literacy”, “fortifying professional identity”, “increasing assessment confidence and agency”, and “fostering a fair and just assessment”. Furthermore, it was found that TAI led to teachers’ professional success by “increasing students’ academic emotions and outcomes”, “enhancing teachers’ community recognition and reputation”, “aligning and fulfilling teaching, assessment, and curriculum objectives”, and “boosting teachers’ positive psycho-emotional factors”. These findings collectively suggest that TAI operates as a meta-competency—one that transcends the conventional boundaries between assessment capacity and broader professional growth in L2 education.